Strategi Pemasaran Pegadaian Syariah di Kota Jambi - Nurlaila Nurlaila; Habriyanto Habriyanto; Ayub Mursalin; Wildan Nur Hidayat (ITB AAS INDONESIA Surakarta, 2023)
This thesis aims to: (1) Know the marketing strategy that has been carried out by Islamic Pawnshops in the city of Jambi, (2) Know the obstacles faced by Islamic Pawnshops in the city of Jambi in carrying out the marketing strategy, (3) Know the solutions of Islamic Pawnshops in the city of Jambi in executing a marketing strategy. This study uses a qualitative method. The method used to collect data in this study is through interviews, observation and documentation. The results of this study are (1) The marketing strategies that have been carried out by Islamic Pawnshops in the city of Jambi, namely: Strategies in the fields of product, price, distribution, and promotion, (2) The obstacles encountered occur due to internal and external factors. The internal factors of employees who concurrently serve as human resources at the Jambi City Sharia Pawnshop fully understand Sharia principles, have not yet optimized technology and social media. While external factors are business competition with other financial institutions, the lack of public understanding of Pegadaian Syariah, (3) Solutions in implementing marketing strategies by recruiting HR with more expertise, providing training and coaching to employees and activating social media and launching attractive products for the community . The marketing strategy that has been implemented by Pegadaian Syariah in the city of Jambi has been carried out well, although there are still improvements and improvements in marketing being carried